The locksmith [videorecording (DVD)] - Phillippe, Ryan, 1974-; Bosworth, Kate, 1983-; Rhames, Ving, 1961- (Screen Media Films, 2023)
An expert locksmith is released from prison and pulled back into a world of crooked cops and small-town gangsters, despite the future he hoped to build with his ex-fiance and their daughter.